The Relationship between Maternal Characteristics and Folic Acid Intake with the Incidence of Anemia in Pregnant Women in Percut Sei Tuan District - Mahdiah Mahdiah; Atika Salma Rahmadani (International Journal of Social Service and Research, 2023)
Anemia is a nutritional problem with a high prevalence. Anemia often occurs in teenagers, women of childbearing age, and pregnant women. This study aims to determine the relationship between maternal characteristics and folic acid intake with the incidence of anemia in pregnant women. The design of this study is cross sectional. The population is all pregnant women in the second and third trimesters in three villages in the Percut Sei Tuan sub-district. The sampling in this research was porpusive sampling. Data collection was carried out through interviews using questionnaires and food recall tables as research instruments. Data processing through editing, entering and tabulating. Data analysis used the Chi Square test with Ci 95%. The results of the study showed that 87.8% of mothers in the good age group did not experience anemia and 12.1% of mothers in the unfavorable age group experienced anemia. 90.2% of mothers in the good parity group were not anemic and 9.8% of mothers in the poor parity group were anemic. 90.2% of mothers with good ANC group experienced anemia and 9.8% of mothers with poor ANC group did not experience anemia. 9.8% of pregnant women in the good folic acid intake group were not anemic and 48.8% of pregnant women in the not good folic acid intake group were anemic. There is a relationship between parity, ANC visits and folic acid intake in pregnant women in Percut Sei Tuan District. And there is no relationship between maternal age and the incidence of anemia in Percut Sei Tuan District.